2015
DOI: 10.1186/s40885-016-0039-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram derived QRS duration associations with elevated central aortic systolic pressure (CASP) in a rural Australian population

Abstract: BackgroundProlonged electrocardiogram QRS durations are often present in hypertensive patients. Small increases in QRS duration serve as independent risk factors for both increased cardiovascular and all-cause mortality. Aortic stiffness is associated with increases in central aortic systolic blood pressure (CASP). However CASP and ECG QRS duration interactions have not been established in rural community populations. Our aims are to determine if QRS duration > 100 msec is associated with an elevated CASP meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…On the other hand, the mean age of our study population was 68.2 years, where central aortic stiffening could theoretically influence systolic blood pressure changes that could increase QRS duration (over a short period of time). A previous cross-sectional study, representative of our study population, demonstrated higher than expected central aortic blood pressure [23] in rural Australia. Many of the risk factors that comprise the Framingham risk score can influence QRS duration.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…On the other hand, the mean age of our study population was 68.2 years, where central aortic stiffening could theoretically influence systolic blood pressure changes that could increase QRS duration (over a short period of time). A previous cross-sectional study, representative of our study population, demonstrated higher than expected central aortic blood pressure [23] in rural Australia. Many of the risk factors that comprise the Framingham risk score can influence QRS duration.…”
Section: Discussionsupporting
confidence: 49%
“…We do not have data on medications that may have influenced QRS duration in this study. On the other hand, we appreciate that in rural areas of Australia medication use and compliance is low for cardiovascular medications [23,24]. Additionally, we do not have strict diagnosis of whether bundle branch block was evident at higher QRS durations in our population.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that aging-associated cardiac dysfunction is related to an aged condition accompanying telomere shortening in somatic cells. [12][13][14][15][16][17][18] Therefore, electro-or echocardiographic variables can be indices of individual genomic aging.…”
Section: Discussionmentioning
confidence: 99%
“…People 25–65 years of age who are listed in the voter list of 2007 are eligible for inclusion in the baseline survey. The primary endpoint of the study is a reduction in SBP, because with aging there is an increase in SBP due to aortic stiffening [ 24 ]. This may not be modifiable through reduction in risk factors.…”
Section: Methodsmentioning
confidence: 99%